Cape Verde - Enhancing Planning to Increase Efficiency of Public Spending : Background chapters - World Bank (World Bank, 2012)
A Public Expenditure Review (PER) update was conducted in 2006 which highlighted: (i) the large and increasing weight of non-discretionary expenditures in the total budget; (ii) the importance of improving coordination among the various planning instruments; (iii) the need to strengthen public finance management; (iv) the fiscal risks that emerge from the energy sector; and (v) the need to further progress with the pension reform. During 2006-07 the Government implemented several of the 2006 PER update recommendations. Building on the findings of the 2006 PER update, in mid 2007 the Government and the World Bank decided to prepare jointly an updated PER that would inform the preparation of the second Growth and Poverty Reduction Strategy Paper (GPRSP-2) and the Country Assistance Strategy (CAS). The objectives of the PER were to: (i) examine recent macro and fiscal developments (chapter one and two); (ii) provide an update of the strengths and shortcomings of the public finance management system, the recent reforms implemented in this area and the new emerging challenges (chapter three); (iii) conduct an analysis of the fiscal decentralization issues, with particular emphasis on the municipalities' resources, expenditures, budget processes, capacity and systems, and accountability to the citizens (chapter four); and (iv) examine public expenditure issues in infrastructure, focusing on issues of adequacy, allocation and efficiency of spending in electricity, water, roads, air transportation, and ports (chapter five).